2016
DOI: 10.1111/bju.13460
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility for active surveillance in biopsy Gleason 3 + 4 prostate cancer: an Australian radical prostatectomy cohort

Abstract: Retrospective review of 929 patients, with biopsy proven GS 3 + 3 and 3 + 4 PCa, undergoing upfront radical prostatectomy (RP) was performed. Suitability for AS was adapted from protocols by Royal Marsden Hospital, University of Toronto, and PRIAS by allowing Gleason 3 + 4 disease.The outcomes assessed were adverse pathology at RP (upgrading ≥GS 4 + 3 and/or upstaging ≥pT3) and biochemical recurrence (BCR) after RP. ResultsAdverse pathology at RP was compared between GS 3 + 3 vs 3 + 4 groups. When selecting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Other potential factors driving the observed variation in active‐surveillance rates that cannot be addressed by the current data might include legal fears regarding the underestimation of prostate cancer aggressiveness, a family history of prostate cancer, and patient‐related psychological factors . The aforementioned factors may explain why surveillance uptake is exceptionally low in the United States in comparison with other Western economies such as the European Union . Consequently, it will be important to tout the results of the many ongoing trials aimed at providing decision aids to men newly diagnosed with prostate cancer, which may help to mitigate some of the common misconceptions surrounding prostate cancer treatment and survival …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other potential factors driving the observed variation in active‐surveillance rates that cannot be addressed by the current data might include legal fears regarding the underestimation of prostate cancer aggressiveness, a family history of prostate cancer, and patient‐related psychological factors . The aforementioned factors may explain why surveillance uptake is exceptionally low in the United States in comparison with other Western economies such as the European Union . Consequently, it will be important to tout the results of the many ongoing trials aimed at providing decision aids to men newly diagnosed with prostate cancer, which may help to mitigate some of the common misconceptions surrounding prostate cancer treatment and survival …”
Section: Discussionmentioning
confidence: 98%
“…9,37 The aforementioned factors may explain why surveillance uptake is exceptionally low in the United States in comparison with other Western economies such as the European Union. 38,39 Consequently, it will be important to tout the results of the many ongoing trials aimed at providing decision aids to men newly diagnosed with prostate cancer, which may help to mitigate some of the common misconceptions surrounding prostate cancer treatment and survival. 40 Our findings suggest that urologists have been critically poor at enrolling low-risk patients into activesurveillance protocols, and this is supported by past literature.…”
Section: Discussionmentioning
confidence: 99%
“…Given the differences in PCa‐specific mortality rates for patients with Grade Group 2 and Grade Group 3 disease, decisions regarding the proper interventions at the correct time for these Grade Groups are a subject of debate, especially for a subset of Grade Group 2 patients who potentially qualify for management through active surveillance based on age and remaining lifespan . However, there are patients with Grade Group 2 disease who develop tumor progression (between 7.1% and 50.6% of patients undergo reclassification, depending on the study) and those with Grade Group 3 disease whose tumors remain slow‐growing . Therefore, discriminating between tumors that behave indolently from those that progress is a key unmet clinical need, specifically for tumors with intermediate histopathologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…We found significantly higher levels of PBOV1 protein in samples with Grade Group 3 and above in comparison to samples of Grade Group 1 and 2. Further analysis revealed significant differences between protein levels in Grade 32 and those with Grade Group 3 disease whose tumors remain slowgrowing. 33 Therefore, discriminating between tumors that behave indolently from those that progress is a key unmet clinical need, specifically for tumors with intermediate histopathologic findings.…”
Section: Review Of Our Findings With Recent Publicationsmentioning
confidence: 97%
“…Surgical technique has however evolved since the previous study to performing nerve-sparing prostatectomies where possible and thus more recently, a large Swedish study reported an incontinence rate of 21.3% following RALP at the same time point (2,3). While the incidence of UI has pleasingly decreased over time, it still has a significant impact on the quality of life following surgery, which partly explains the preference to manage patients on active surveillance where suitable (4). Abraham and colleagues reported that worsening urinary function negatively impacts patient satisfaction post-radical prostatectomy (RP) (5).…”
Section: Introductionmentioning
confidence: 99%